A systematic review and meta-analysis comparing the efficacy and safety of ciprofol (HSK3486) versus propofol for anesthetic induction and non-ICU sedation - Hung, Kuo-Chuan; Chen, Jen-Yin; Wu, Shao-Chun; Huang, Po-Yu; Wu, Jheng-Yan; Liu, Ting-Hui; Liu, Chien-Cheng; Chen, I-Wen; Sun, Cheuk-Kwan (Frontiers in Pharmacology, 2023)
Background: Ciprofol (HSK3486) is a novel intravenous anesthetic agent that bears structural similarity to propofol and displays favorable pharmacodynamic characteristics such as rapid onset and offset. The meta-analysis aimed at comparing the efficacy and safety of ciprofol versus propofol in clinical practice.: Medline, EMBASE, Google Scholar, Cochrane Library were searched from inception to April, 2023. The primary outcome was success rate of sedation/anesthetic induction and differences in sedation/induction time. The secondary outcomes included risks of hemodynamic instability, respiratory complications, and pain on injection, as well as recovery profiles, satisfaction score, and top-up dose requirement. Results: Twelve RCTs (sedation: n=6, anesthetic induction, n=6, all conducted in China) involving 1793 patients (age: 34 to 58 years) published from 2021 to 2023 were analyzed. Pooled results revealed no differences in success rate [risk ratio (RR)=1, 95% confidence interval (CI): 0.99 to 1.01, I 2 =0%, 1106 patients, p=1) and time required for successful anesthetic induction/sedation [mean difference (MD)=7.95 seconds, 95% CI: -1.09 to 16.99, I 2 =97%, 1594 patients, p=0.08). The risks of top-up dose requirement (RR=0.94, p=0.48), cardiopulmonary complications [i.e., bradycardia (RR=0.94, p=0.67), tachycardia (RR=0.83, p=0.68), hypertension (RR=1.28, p=0.2), hypoxemia/pulmonary depression (RR=0.78, p=0.24)], and postoperative nausea/vomiting (RR=0.85, p=0.72), as well as discharge time (MD=1.39 minutes, p=0.14) and satisfaction score (standardized MD=0.23, p=0.16) did not differ significantly between the two groups. However, the ciprofol group had lower risks of hypotension (RR=0.85, p=0.02) and pain on injection (RR=0.17, p<0.00001) than the propofol group. The time to full alertness was statistically shorter in the propofol group (i.e., 0.66 min), but without clinical significance.Our results demonstrated similar efficacy between ciprofol and propofol for sedation and anesthetic induction, while ciprofol was associated with lower risks of hypotension and pain on injection. Future studies are warranted to evaluate the efficacy and safety of ciprofol in pediatric or the elderly populations.